The Material Conditions of Thought. Body, force, and faculty in the Allgemeine Naturgeschichte - Costantini, Marco (Con-Textos Kantianos. International Journal of Philosophy, 2023)
The contribution examines the third part of the Allgemeine Naturgeschichte, written by Kant in 1755, and focuses in particular on the mind-body relationship. In particular, the contribution highlights the presence of two layers in Kantian discourse. In the first one, the body is considered a limitation of the spirit, which would fully develop its cognitive faculties if it were not tied to a matter. In the second one, on the contrary, the body, or rather the material quality of the body, gives the spirit the ability to exercise the power of thought.